PLASMID PROFILING OF EXTENDED SPECTRUM Β-LACTAMASES PRODUCING ESCHERICHIA COLI IN SOME HOSPITALS IN BAGHDAD - M. ATIF; D.S.AL-Rubaye; H. R. Al-Hraishawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study was aimed to determine the prevalence of ESBLs in E. coli and their relation to plasmid profiling patterns in a sample of patients in Iraqi hospitals. The total number of E. coli isolates 91 (49%) were collected out of 185 clinical samples. The antibiotic sensitivity test for isolates showed high resistance percentage to Nitrofurantion 95.7%, amoxicillin and Ceftriaxone to each of which 91.3% and to Ceftazidime 90.2%, while the highest sensitivity was observed against Imipenem 100%, Meropenem 99% then to Amikacin 93.5%. The Multi drug resistant (MDR) isolates were 53(58.2) % and ESBLs producers were 45 (49.5) %. Plasmid profile analysis showed nineteen different plasmid profile patterns were obtained based on molecular weight and number of plasmids content. Most β-lactamase producers had multiple plasmids, where’s single plasmid profile predominant in non-β-lactamase-producing isolates. The presence of common plasmid among the isolates increases the distribution of resistant plasmid in the community. In conclusion, ESBLs producing bacteria can transferred between species by plasmids leading to cross resistance which give a limited options for treatment.